HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN PERAN PETUGAS KESEHATAN DENGAN PENERIMAAN VAKSINASI COVID-19 OLEH MASYARAKAT DI KELURAHAN PANIKI BAWAH - Rawung, Gladys Maristela; Kaunang, Wulan P. J.; Mantjoro, Eva M. (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Covid-19 vaccination as a government policy program around the world that aims to reduce the transmission of Covid-19. In this study, the design used was a cross sectional design. This research was conducted in the Paniki Bawah sub-district in October - November 2022. The population for this study was the entire community in the Paniki Bawah sub-district, totaling 12,191 people based on population data from Paniki Bawah Sub-district in 2022 with a research sample of 263 respondents. This study used a consecutive sampling approach. The results showed that most respondents had received complete vaccination (75.3%), good knowledge (79.8%), poor family support (61.2%) and a good role of health workers (59.7 %). The results of the bivariate analysis of knowledge have a sig value. of 0.024 (<0.05) which means that there is a significant relationship between knowledge and acceptance of the Covid-1 vaccination, family support has a sig value. of 0.000 (<0.05) which means that there is a significant relationship between family support and acceptance of the Covid-19 vaccination and for the role of officers obtains a sig value. of 0.544 (> 0.05), which means that there is no relationship between the role of health workers and acceptance of Covid-19 vaccination. There is no relationship between health and the receipt of the Covid-19 vaccination in the Paniki Bawah Village. Then the most dominant variable is family support by receiving the Covid 19 vaccination in Paniki Bawah Village.